Analysis of the Influence of Brand Image and Product Variety on Purchasing Decisions for Wizzmie in Sidoarjo Regency (International Journal of Scientific Research and Management (IJSRM), 2024)
The goal of this study is to explore at how brand image and product diversity effect consumer purchasing decisions for Wizzmie in Sidoarjo Regency. A quantitative research approach, including a survey procedure, was employed. Wizzmie clients were requested to fill out surveys in order to collect primary data. The data was analysed using multiple linear regression techniques. The study’s findings imply that brand image has a favourable and significant influence on client buying decisions. Product diversity has a substantial positive impact on buying decisions. As a result, both brand image and product variety impact Wizzmie consumers’ purchase decisions in Sidoarjo Regency. This research implies that companies should pay attention to and enhance their brand image and product variety to improve consumer purchasing decisions. It is hoped that this will help companies in designing more effective marketing strategies.